THE READING STRATEGIES AND READING COMPREHENSION OF THE HEALTH ANALYST DEPARTMENT STUDENTS - Wisnu Istanto (Widya Mandala Surabaya Catholic University, 2016)
This research focused on the issue of the reading strategies and reading comprehension of the Health Analyst Department students. The Health Analyst Department students need reading strategies to acquire knowledge according to their specific needs. They need to be able to comprehend their target texts. This research aimed to identify the Health Analyst Department students’ reading strategies and reading comprehension achievement as well as to correlate their reading strategies to reading comprehension. This research employed qualitative method. The research utilized Mokhtari and Sheorey’ (2002) survey of reading strategies (SORS) and reading comprehension test (RCT) as research instruments. All research data of reading strategies (global, problem solving and support reading strategies) and reading comprehension were analyzed by using descriptive statistics, linear regression and Pearson’s Product Moment correlation test. The students frequently utilized the problem solving reading strategies in comprehending their target texts. The correlation coefficient of support reading strategies is greater than the two others. Those results give indications that the students’ choices of reading strategies do not always give better reading comprehension. The students’ reading strategies have significant positive correlation to their reading comprehension with regard to their comprehending the target texts.